Evolution and Expression of the Immune System of a Facultatively Anadromous Salmonid - Colgan, Thomas J.; Moran, Peter A.; Archer, Louise C.; Wynne, Robert; Hutton, Stephen A.; McGinnity, Philip; Reed, Thomas E. (Frontiers in Immunology, 2021)
Vertebrates have evolved a complex immune system required for the identification of and coordinated response to harmful pathogens. Migratory species spend periods of their life-cycle in more than one environment, and their immune system consequently faces a greater diversity of pathogens residing in different environments. In facultatively anadromous salmonids, individuals may spend parts of their life-cycle in freshwater and marine environments. For species such as the brown trout Salmo trutta, sexes differ in their life-histories with females more likely to migrate to sea while males are more likely to stay and complete their life-cycle in their natal river. Salmonids have also undergone a lineage-specific whole genome duplication event, which may provide novel immune innovations but our current understanding of the differences in salmonid immune expression between the sexes is limited. We characterised the brown trout immune gene repertoire, identifying a number of canonical immune genes in non-salmonid teleosts to be duplicated in S. trutta, with genes involved in innate and adaptive immunity. Through genome-wide transcriptional profiling (“RNA-seq”) of male and female livers to investigate sex differences in gene expression amplitude and alternative splicing, we identified immune genes as being generally male-biased in expression. Our study provides important insights into the evolutionary consequences of whole genome duplication events on the salmonid immune gene repertoire and how the sexes differ in constitutive immune expression.